1996
DOI: 10.1111/j.1750-3639.1996.tb00856.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Demyelinating Diseases

Abstract: Multiple sclerosis (MS), the prototypic demyelinating disease in humans, is the most common cause of acquired neurological dysfunction arising between early to mid adulthood. MS is an inflammatory disorder and is believed to result from an autoimmune response, directed against myelin proteins and perhaps other antigens, resulting in demyelination and dense astrogliosis. A genetic component in MS is indicated by an increased relative risk to siblings compared to the general population (lambda s) of 20-40, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 82 publications
0
23
0
Order By: Relevance
“…Similar mono-and dizygotic twin concordance rates of 30 and 4%, respectively, in both MS and diabetes suggest that environmental factors trigger and/or sustain autoimmunity through interaction with the products of predisposing genes (5,6). The search for viral triggers of autoimmunity has continued for decades.…”
Section: Ultiple Sclerosis (Ms)mentioning
confidence: 92%
“…Similar mono-and dizygotic twin concordance rates of 30 and 4%, respectively, in both MS and diabetes suggest that environmental factors trigger and/or sustain autoimmunity through interaction with the products of predisposing genes (5,6). The search for viral triggers of autoimmunity has continued for decades.…”
Section: Ultiple Sclerosis (Ms)mentioning
confidence: 92%
“…21 Genetic studies indicate MS is likely to be a polygenic disorder, due to multiple gene associations. [22][23][24] Some of the genes reported to be associated with MS include interleukin, 25,26 CTLA4, 27 HLA-DRB1*1501, and apolipoprotein E. 28 Early-published reports 29,30 of epidemiological studies of MS concluded that the disease was common in persons of Scandinavian descent: an ethnic group that exhibits a high prevalence of CCR5 ⌬32 mutation. Among the European white population there is a north to south gradient of prevalence of the CCR5 ⌬32 mutant allele, with the allelic frequencies highest in Scandinavia (16%) and lowest in Sardinia (4%), with a mean allelic frequency across the whole of Europe of 9.1%, where as this variant was found in only 1% in individuals of African origin, 0% in Asians, and 9.8% in Caucasians.…”
mentioning
confidence: 99%
“…21 Genetic studies indicate MS is likely to be a polygenic disorder, due to multiple gene associations. [22][23][24] Some of the genes reported to be associated with MS include interleukin, 25,26 CTLA4, 27 HLA-DRB1*1501, and apolipoprotein E. 28 Early- …”
mentioning
confidence: 99%
“…Pathogenic CD4 + T cells in these diseases are thought to express T cell receptors (TCRs) that recognize specific peptides bound to class II major histocompatibility complex (MHC) proteins on the surface of antigen-presenting cells (APCs), where the presented peptide is derived not from a pathogen, but from an allergen, transplant antigen, or self protein. Specific peptides derived from allergens or "self" proteins have been identified as linked to the pathological responses in many cases (Haselden et al 1999;Hemmer et al 1998;Jahn-Schmid et al 2002;Muraro et al 1997;Reijonen et al 2002;Vergelli et al 1997), and links between particular class II MHC alleles and disease susceptibility have been identified (Ebers et al 1996;Oksenberg et al 1996;Wucherpfennig & Sethi 2011). Hence, one attractive option would be to selectively inhibit only those CD4 + T cells that initiate or sustain pathological inflammation.…”
Section: Background: Inflammatory Diseasesmentioning
confidence: 99%